For the common good : principles of American academic freedom - Finkin, Matthew W.; Post, Robert, 1947- (Yale University Press, 2009)
This book offers a concise explanation of the history and meaning of American academic freedom, and it attempts to intervene in contemporary debates by clarifying the fundamental functions and purposes of academic freedom in America.--From publisher description.